A systematic review and meta-analysis of surgeries performed for treating deep-seated cerebral cavernous malformations. (4th July 2015) - Qiao, Nidan; Ma, Zengyi; Song, Jianping; Wang, Yongfei; Shou, Xuefei; Zhang, Xiaoluo; Shen, Ming; Qiu, Huijia; Ye, Zhao; He, Wenqiang; Li, Shiqi; Fu, Chaowei; et al.
Abstract: Objective. The clinical benefit of surgery for treatment of deep-seated cerebral cavernous malformations (CCMs) is still a matter of debate. Although the surgical removal of CCMs is widely accepted, the benefits of reducing the rate of haemorrhage must be balanced against the risk of peri-operative morbidity. Here, we provide a systematic review and meta-analysis of the clinical benefits of surgery for treating deeply localised CCMs. Methods. A comprehensive search of PubMed and Embase was conducted to identify relevant studies. The rate and a 95% confidence interval (CI) were used to measure the risk of haemorrhage and adverse outcomes. Results. A total of 34 cohort studies reporting surgeries on CCMs were included in our analysis. Overall, the average post-surgical haemorrhage rate was 1.0% (95% CI: 0.7–1.4%). Nine per cent (95% CI: 6.9–11.3%) of the patients developed adverse events at follow-up following the surgical resection of deep-seated CCMs. The percentage of transient neural defects following surgical resection was 34.6% (95% CI: 29.4–39.9%). The proportions of transient focal neurological defect before and after the year 2006 were 44.9% (95% CI: 34.1–55.8%) and 30.3% (95% CI: 25.1–35.9%), respectively. Conclusions. Our meta-analysis demonstrates post-surgical haemorrhage rate and complications related to surgeries on deep-seated CCMs. The post-surgical haemorrhage rate was low with a relatively high rate of post-surgical complications.